Research to support optimization of prescription drug monitoring programs. Issue 11 (14th September 2017) - Doyle, Sheri; Leichtling, Gillian; Hildebran, Christi; Reilly, Cynthia
Abstract: Purpose: Research is needed to evaluate the impact of prescription drug monitoring programs (PDMPs). This paper describes research priorities for PDMPs that were initially discussed at a 2015 meeting of PDMP administrators, researchers, public health officials, and other stakeholders. Methods: Meeting participants defined the current landscape of PDMP research and identified research gaps. Research priorities were grouped by theme. Results: Prescription drug monitoring program research priorities were identified for 3 key areas: individual patient health outcomes, prescriber use and decision making, and population‐level outcomes. Research areas for individual patient outcomes include examining drug‐use thresholds that best predict risk for overdose or substance use disorder and unintended consequences of PDMP use. Proposed research on prescriber PDMP use include evaluating how enhancements to the content and format of PDMP reports informs clinical decision making and optimal clinician actions in response to a concerning PDMP report. Finally, research topics related to population‐level outcomes include measuring the impact of PDMP policies on the incidence of substance misuse and harms and assessing the return on investment for these databases. Conclusions: The clinical, public health, and economic impacts of PDMPs must be evaluated, using both quantitative and qualitative methods. In addition to assessing patient outcomes, qualitative research should examine how clinicians use and interpret PDMP information. Research should also examine the impact of PDMP features and policies on prescriber utilization. Comparative analyses across states with differing PDMP policies should be conducted to inform best practices.